Tinjauan Yuridis Terhadap Obyek Jaminan Fidusia yang Digadaikan Tanpa Persetujuan Penerima Fidusia (Studi Kasus di PT. Sinarmas Multifinance Cabang Jember) - Cipta Nurrovik , M. Dani; Reykasari, Yunita (Indonesian Journal Publisher, 2023)
This research examines the juridical review of fiduciary collateral objects pledged without the consent of the fiduciary recipient. The aim of this research is to analyze the juridical review of fiduciary collateral objects pledged without the consent of the fiduciary recipient. The research method used is the statutory approach method (statue approach) and the case approach method. The type of research is normative juridical, meaning that the problems raised, discussed and described in this research are prioritized by applying positive rules or norms. The research results reveal that in practice we encounter many cases with obstacles in the field. Firstly, this is because many fiduciary recipients still do not register fiduciary collateral objects. Second, fiduciary parties can still be found who violate the agreed provisions. Even though the object of the fiduciary guarantee has been registered, there are still fiduciary providers who pledge the object of the fiduciary guarantee. The form of formal legal protection that can be done is by registering the object of fiduciary collateral with the fiduciary registration office. The second step is to provide a clause to provide sanctions against the party giving the fiduciary.